Book Review: Avijit Pathak, On Social Constraints and the Great Longing: An Essay on the Human Condition. (January 2016) - Priyam, Chayanika
Avijit Pathak, On Social Constraints and the Great Longing: An Essay on the Human Condition, 2014, New Delhi: Aakar Books, pp. 140, ₹ 395, ISBN 978-93-5002-267-2.